Analysis of the implementation value of abdominal B-ultrasound combined with cervical cerclage in the prevention and treatment of late recurrent spontaneous abortion - Lili Shi; Lei Dong; Yuanying Cui; Dan Bu; Bo Hu (BMC Pregnancy and Childbirth)
Abstract Objective To study the implementation value of abdominal B-ultrasound combined with cervical cerclage in the prevention and treatment of recurrent late abortion. Methods From October 2020 to December 2023, 196 pregnant patients who had a history of late abortions at our institution were chosen. They were divided into groups based on the treatments used. In the observational team, 98 instances received abdominal B-ultrasound along with cervical cerclage, while 98 instances in the controlling team underwent traditional conservative treatment. Vaginal flora, inflammatory factor levels, labor outcomes, uterine artery parameters, and adverse effects were observed in both groups of pregnant women. Results Comparing the detection of vaginal flora between the two groups, the difference was not statistically significant (P > 0.05); the detection values of WBC, neutrophil percentage and neutrophil absolute value in the observation group were lower than those in the control group (P < 0.05). The recurrent late abortion rate (4.08%) and premature delivery rate (16.33%) were lower than those of the control group, and the full-term delivery rate (79.59%) and total fetal survival rate (93.88%) were higher than those of the control group, and the difference was statistically significant (P < 0.05). The resistance index (RI) and pulsatility index (PI) of pregnant women with abortion were higher than those of live birth pregnant women. The RI and PI of group A (pregnant women with recurrent late abortion) at 7, 12, 24 and 32 weeks of gestation were also higher than those of group B (pregnant women without recurrent late abortion), and the difference was statistically significant (P < 0.05). At 7 weeks of gestation, there was no statistical difference between the observation and control groups in terms of RI and PI (P > 0.05)0.12 By 32 weeks of gestation, the RI and PI were lower in the observation group than in the control group (P < 0.05)0.13 In the observation group, the RI and PI were lower than in the control group (P < 0.05). The incidence of gestational hypertension, gestational diabetes mellitus, and eclampsia were significantly lower in the observation group compared to the control group (P < 0.05). Conclusion Abdominal ultrasound combined with cervical cerclage reduces the risk of miscarriage by improving the hemodynamic status of the uterus and placenta, and also optimizes the pregnancy environment by reducing the inflammatory response in the uterine cavity, which has important clinical applications in the prevention and treatment of late recurrent spontaneous abortion.